Evaluación de diferentes niveles de inclusión de Trichanthera gigantea en la calidad de la canal de pollos finqueros - Eras Calvopiña, Maily Gicell (2024)
Carcass quality in chickens is a determining factor for the market, and the inclusion of forage plants in poultry feed is an alternative that allows improving the organoleptic characteristics of the final product. The objective of this research was to evaluate the different levels of inclusion of Trichanthera gigantea in the diet of broiler chickens on carcass quality. One hundred and fifty-one-day-old broiler chickens with an average weight of 40 g were randomly distributed in three treatments with different levels of Trichanthera gigantea, T1 (control), T2 (5%), T3 (10%). A completely randomized design was applied. The diets were formulated considering the nutritional requirements of the FEDNA tables for free-range chickens at different stages of production and were fed from 29-71 days of age. Carcass yield, tarsus, skin and thigh pigmentation (pedal and digital flexor muscle) and meat pH variables were evaluated in 30 broilers of 71 days of age with an average weight of 1715 g. The data were analyzed using the statistical program InfoStat, with an analysis of variance (ANOVA) and LSD Fisher was used for the comparison of means. The results show that in pigmentation, the variables b*skin p=0.019 and b*tarsus p=0.001 presented significant differences, determining an effect of the addition of 10% T. gigantea; while the variables L*skin, a*tarsus, b*thigh did not show statistical differences p=0.666 between treatments, as well as carcass yield and thigh pH, obtaining averages of L*63.86, a*3.02, b*-3.8, RC 80.2% and pH 6.6, respectively. It is concluded that the inclusion of Trichanthera gigantea had a positive effect on the variable yellowish pigmentation (b*) in tarsus and skin in broiler chickens.